Pharmaceutical compounds in Malaysian urban domestic wastewater - Zarimah Mohd Hanafiah,; Wan Hanna Melini Wan Mohtar,; Nur Aina Bachi’,; Haris Hafizal Abd Hamid,; Teh Sabariah Abd Manan,; Indarto, Antonius (Penerbit Universiti Kebangsaan Malaysia, 2022)
The emerging contaminants (ECs) is detected at trace concentration in the discharge of sewage treatment plant (STP) to the water bodies indicate incomplete removal during the treatment process. The presence of the ECs in the water has a potential impact on the ecological and human health associated with long-term ingestion of the mixture ECs compounds, and this includes the development of resistance in pathogenic bacteria, aquatic toxicity, genotoxicity, and endocrine disruption. In this study, we investigate the presence of ECs and review the occurrence of mainly of four pharmaceutical active compounds belonging to the group of non-steroidal anti-inflammatory drugs (NSAIDs) in influent and effluent of the STP. The target analytes (ibuprofen (IBU), diclofenac (DIC), ketoprofen (KET), and naproxen (NAP)) are extracted from the wastewater using the solid-phase extraction (SPE) followed by the identification and quantification using gas chromatography-mass spectrometry (GC-MS). The GC-MS detection was improved by the derivatisation technique using N-Methyl-N-(trimethylsilyl)trifluoroacetamide (MSTFA) and an internal standard of Ibuprofen-D3 used as the internal standard. The targeted analytes were detected in both influent and effluent wastewater in the range 5.04±5.9 to 37.4±28.4 μg/L with removal efficiency between 11 - 86% using the current activated sludge treatment process in the STP. This concentration of compounds shows inadequate current treatment techniques to eliminate the emerging contaminants in the wastewater.